Reasons for extracting children's teeth at the department of pediatric dentistry, RSGM Baiturrahmah - Utami, Sri Pandu; Suryati, Sisi I (Politeknik Kesehatan Kemenkes Aceh, 2023)
Background : Extraction of primary teeth is a relatively common part of pediatric dentistry practice, often included as part of treatment based on caries, trauma, and orthodontic considerations. Object: The samples were 30 children who had their teeth extracted at RSGM Baiturrahmah. Research Methods: Research by filling out informed consent Research by interview was asked directly to the mother and child during the anamnesis before the child had a tooth extraction in the room. Results: The results of the study were based on a sample of 30 children who had their teeth extracted at the Baiturrahmah Hospital, the highest number was the extraction of the incisors as many as 14 children on the grounds that the teeth were loose or the teeth were persistent, 8 children extracted the 1st molars because the teeth had been lost. rocking and cavities. 7 children had their 2nd molars extracted and 1 child had their canines extracted due to loose teeth and cavities. Conclusion: Based on the reasons why children do tooth extraction, that is because dental caries is the most common cause, followed by mobility and persistence.